Anorectal Malformations and Posterior Sagittal AnorectoplastyA Prospective Study for a Period of One Year in North-West Punjab - Amarjit Singh Kuka; Nishan Singh; SP Singla; Pushpinder Singh Kuka (JCDR Research and Publications Pvt. Ltd., 2016)
Introduction: Anorectal Malformations (ARM) have enormous impact on the patient's quality of life. It is not only a surgical challenge but also a shocking event for parents and whole family. Despite of advances in field of surgery, it challenges the wisdom and expertise of surgeons. Aim: To determine the incidence of ARM in North West Punjab and to evaluate the success of different types of surgeries such as Posterior Sagittal Anorectoplasty (PSARP), Anterior Sagittal Anorectoplasty (ASARP) and cut back anoplasty. The prevalence of bowel continence after surgery for high or low ARM was also studied along with proportion of cases requiring colostomy. Materials and Methods: A prospective study was done in thirty (30) patients having ARM in North-West region of Punjab, admitted over a period of one year. In low varieties of ARM, the primary surgery was done at the time of presentation. In high and intermediate varieties, primary defunctioning colostomy was done at the time of presentation followed by definitive repair later. In majority of patients definitive repair was done by PSARP, in few cases by ASARP and very few cases PSARP combined with Abdominal pull through approach. Colostomy closure was done after 4-6 weeks of regular anal dilatation. Results: The male to female ratio was 1:1, with 60% patients presenting in neonatal period and 40% in post neonatal period. The level of lesion was high in 46.66%, intermediate in 13.33%, and low in 30% patients. Cloaca was seen in 10% of cases. The common presenting symptoms were not passing meconium since birth (50%), absent or abnormal anal opening, vomiting (13.33%) with increasing abdominal distension (26.66%), excessive crying and passing of thin pipe stools with constipation (23.33%), passing stools through vagina (13.33%) or urethra (3.33%) or an abnormal opening elsewhere in the perineum (20%). Associated urogenital anomalies were seen in 13.33% cases. Other anomalies included Meckel's diverticulum (6.66%), pouch colon (3.33%), bicornuate uterus (3.33%) hypospadias with meatal stenosis (3.33%), undescended testes (3.33%), Inguinal hernia (3.33%), bilateral choanal atresia (3.33%), band at ileo caecal region (3.33%) and terminal ileum opening in caecum attached to recto sigmoid region (3.33%). Associated fistulae were seen in 16.66% of patients. Overall morbidity of the definitive procedure was 31.58% and mortality was 10% in present study. Conclusion: In majority of patient's definitive repair can be done by PSARP, ASARP PSARP combined with abdominal pull-through approach. Primary PSARP can be tried in rectovestibular, rectovaginal fistula and in some low varieties of ARM.